3α5β-Pregnanolone glutamate, a use-dependent NMDA antagonist, reversed spatial learning deficit in an animal model of schizophrenia - Vales, Karel; Rambousek, Lukas; Holubova, Kristina; Svoboda, Jan; Bubenikova-Valesova, Vera; Chodounska, Hana; Vyklicky, Ladislav; Stuchlik, Ales (Behavioural brain research, 2012)
Neuroactive steroids modulate receptors for neurotransmitters in the brain and thus might be efficacious in the treatment of various diseases of the central nervous system such as schizophrenia. We have designed and synthetized a novel use-dependent NMDA receptor antagonist 3α5β-pregnanolone glutamate (3α5β-P-Glu). In this study, we evaluate procognitive properties of 3α5β-P-Glu in an animal model of schizophrenia induced by systemic application of MK-801. The procognitive properties were evaluated using active place avoidance on a rotating arena (Carousel maze). We evaluated effects of 3α5β-P-Glu on the avoidance, on locomotor activity, and anxiety. 3α5β-P-Glu alone altered neither spatial learning nor locomotor activity in control animals. In the model animals, 3α5β-P-Glu reversed the MK-801-induced cognitive deficit without reducing hyperlocomotion. The highest dose of 3α5β-P-Glu also showed anxiolytic properties. Taken together, 3α5β-P-Glu may participate in the restoration of normal brain functioning and these results may facilitate the development of new promising drugs improving cognitive functioning in schizophrenia.
Keywords: modely nemocí na zvířatech; pregnanolon; Male; Pregnanolone; kognitivní poruchy; Dizocilpine Maleate; dizocilpinmaleát; Schizophrenia; Rats, Long-Evans; učení vyhýbat se; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; Glutamates; vokalizace zvířat; Schizophrenic Psychology; Avoidance Learning; krysa rodu Rattus; úzkost; glutamáty; Animals; schizofrenie (psychologie); zvířata; pohybová aktivita; Cognition Disorders; Rats; schizofrenie; Disease Models, Animal; Motor Activity; Vocalization, Animal; potkani Long-Evans; Dose-Response Relationship, Drug; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; Anxiety